Participatory varietal selection in rice in the Punjab - Mali, Santosh Sambhaji; Virk, Daljit S.; Singh, K.B.; Witcombe, John R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Participatory varietal selection (PVS) was used to try to identify an alternative to the most popular rice variety, Pusa 44, in the Patiala district of the Punjab. Pusa 44 (released in 1993 in India but not recommended for the Punjab) is grown in over 50% of the rice area in Patiala. It is highly susceptible lo bacterial leaf blight (BLB) but is preferred by famers because of its high yield and resistance to lodging. Pusa 44 is late maturing and needs to be transplanted very early in the season--as early as the first week in May, when temperatures are very high. This greatly increases demand for irrigation water and accelerates the lowering of the water table, a serious problem in Patiala and the Punjab. It also causes an increase in humidity in Ihe hot season, contributing to the builld-up of insect populations on the rice, which is a continuous host after the harvest of sunflower. Because of the lack of a suitable alternative, no recommended variety has replaced Pusa 44 so far.